An approach for the use of Learning Objects in teaching computer programming concepts - Begosso, Luiz Ricardo; Begosso, Luiz Carlos; Begosso, Raissa Helena (2016 IEEE Frontiers in Education Conference (FIE), 2016)
The teaching of algorithms and programming concepts to students of the first years of Computer Science course has been a major challenge, because students often have difficulty understanding the subject, leading to a high dropout rate. At our institution, dropout rate in the first year of the Computer Science course is 26%, which led us to think of pedagogical strategies to reduce this number. The use of Learning Objects (LO) has gained ground in higher education, but few experiments have been developed to help teach programming concepts to students in the early years. In other experiments, we applied the use of LO in the teaching of programming concepts. However, one of the difficulties encountered in our previous experiences was to identify the ideal moment to introduce the LO to students. Therefore, in 2015 we conducted a new experiment with two groups of students, using a LO to teach Sorting concepts. For the first group we introduced the LO before the professor started teaching theoretical concepts. For the second group, the professor initially taught the theoretical concepts, and only later was the LO introduced. This study aims to present the methodology used to carry out the experiment and the results achieved.